High-level erythroid expression of human alpha-globin genes in transgenic mice. - Ryan, T M (1989)
The human alpha 1-globin gene was fused downstream of two erythroid-specific DNase I super-hypersensitive sites that are normally located upstream of the human beta-globin locus. This construct was injected into fertilized mouse eggs, and expression was analyzed in 16-day fetal livers and brains. All 11 fetuses that contained intact copies of the transgene expressed correctly initiated human alpha-globin mRNA in the erythroid fetal liver but not in brain. Levels of expression ranged from 4% to 337% of endogenous mouse beta-globin mRNA. A human alpha-globin construct that did not contain super-hypersensitive sites was not expressed. These results demonstrate that human beta-globin locus activation sequences can stimulate high levels of human alpha-globin gene expression in erythroid tissue of transgenic mice. The results also provide a foundation for experiments designed to coexpress human alpha- and beta-globin genes in transgenic mice and suggest a feasible approach for production of a mouse model for human sickle cell disease.